Theory of Solar Cell (DSSC) Collection: Advancements in Dye-sensitized Solar Cell Technology (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Dye-sensitized solar cells (DSSCs), also known as Grätzel cells, are electrochemical devicesthat harness electricity by combining the physicochemical features of many materials. From a groundbreakingidea of molecule photovoltaics, these photoconversion devices have progressed to industrialproduction with proven record efficiencies of 14.3. Because of their efficiency, cheap manufacturingcosts, and high aesthetic attraction, DSSC devices may be made for the consumer electronics industry.This paper introduces the basic concepts behind DSSC and discusses how their efficiency might beincreased for widespread use. Future work on efficiency, stability, and production that will be necessaryfor this technology to really represent a breakthrough in the consumer electronics sector is alsomentioned. An analysis of the leading DSSC developers and their current prototypes and products isprovided.